SARS-CoV-2 coinfection in patients with invasive pulmonary aspergillosis: clinical characteristics and prognosis - Mengshu Xie; Xiaofeng Zhu; Ao Ma; Jiaqi Fan; Guangru Fei; Qianqian Zhou; Yan Zhang; Huimei Wu; Xuqin Jiang (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background COVID-19 associated pulmonary aspergillosis (CAPA) has been globally reported to be a life-threatening complication of severe COVID-19. Previous studies primarily focused on an association between secondary Aspergillus infection and elevated mortality risk in COVID-19 patients, while potential confounding factors and alternative pathogenic mechanisms remain insufficiently investigated. The risk factors and outcomes of patients with secondary SARS-CoV-2 infection following invasive pulmonary aspergillosis (IPA) were not been well explored either. Methods This retrospective monocentric study enrolled 152 hospitalized IPA patients with and without SARS-CoV-2 infection from 1 November 2022 to 31 October 2023. The characteristics of IPA patients and related risk factors were investigated, and the relationship between different SARS-CoV-2 infection status and the prognosis in IPA patients was further evaluated. Results Our analysis demonstrated that IPA patients subsequently diagnosed with SARS-CoV-2 infection exhibited significantly elevated mortality risk compared to those without viral coinfection (53.6% vs. 22.9%, P < 0.001). SARS-CoV-2 infection status (OR 3.708; P = 0.001; 95%CI 1.674–8.212), albumin concentration (OR 0.885; P = 0.005; 95%CI 0.813–0.964), and C-reactive protein level (OR 1.007; P = 0.012; 95%CI 1.002–1.013) were statistically significant independent risk factors for prognosis of IPA patients. Subsequent analysis established a multivariate risk prediction model incorporating independent prognostic factors, which exhibited robust discriminative capacity for mortality risk stratification via ROC curve validation (AUC = 0.792, 95%CI 0.721–0.862, P < 0.0001). A statistically significant difference in mortality rate existed between IPA patients with secondary SARS-CoV-2 infection and CAPA patients (63.2% and 33.3%, P = 0.037). Notably, comparative analysis revealed no statistically significant differences in 28-day (22/96, 22.9% vs. 6/18, 33.3%) or 90-day mortality rates (22/96, 22.9% vs. 6/18, 33.3%) between patients with IPA without SARS-CoV-2 infection and IPA patients with secondary SARS-CoV-2 infection. Conclusions IPA patients with secondary SARS-CoV-2 coinfection had a lower mortality compared to those with CAPA. Considering the high mortality rate, more medical cares are needed for these patients.